Pengaruh Price, Fashion Involvement, dan Environmental Awareness Terhadap Minat Beli Pakaian Thrifting (Studi pada Generasi Z di Jakarta) - Maulydia, Amalia; Aditya, Fachri (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of price, fashion involvement, and environmental awareness on the purchase intention for thrifted clothing among Generation Z in Jakarta, both partially and simultaneously. Grounded in consumer behavior theory, this quantitative study employs a purposive sampling technique. The sample consists of 400 respondents, drawn from a population of 2,772,126 individuals using the Slovin formula. Data analysis was conducted using SPSS software version 27. Partial test results indicate that all independent variables significantly influence purchase intention, with calculated t-values exceeding the t-table value (1.966), price (13.353), fashion involvement (16.032), and environmental awareness (16.032). Furthermore, the simultaneous test demonstrates that these three variables collectively exert a significant influence on purchase intention (calculated F-value 414.741 > F-table 2.627; sig. 0.000 < 0.05). The coefficient of determination (R²) of 0.759 indicates that 75.9% of the variation in purchase intention is explained by these three variables, while the remaining 24.1% is influenced by factors outside the research model.